Fiber reinforced concrete: a state of the art - Hogr Z. Hassan; Najmadeen M. Saeed (Discover Materials)
Abstract Fiber-reinforced concrete (FRC) is a type of concrete with added fibers that has become an interesting material for researchers to study its properties and behavior in a variety of scenarios. Fibers are long, thin, needlelike particles that are mixed into a typical cement paste, mortar, or concrete matrix. Researchers conducted various review studies on the use of fiber in concrete mixes to evaluate the changes in concrete properties. However, they had certain limitations because they only looked at one type of concrete or fiber, or how fiber influenced a restricted number of concrete properties. Others have decided to focus solely on recycled fibers, ignoring the effect of industrial fresh fibers on concrete. This work aims to develop an extensive database containing various types of fibers, fiber properties, fiber ratios, concrete mixtures, and aggregate particle varieties. The purpose of this database is to fill in the gaps and weaknesses of previous review papers and provide a comprehensive and detailed analysis of the literature produced by researchers studying fiber-reinforced concrete. The literature defined the effects of fibers in various kinds of use for different types of concrete. The study examines the impacts of fibers on the fifteen main features of concrete, employing 149 literatures that comprise its durability, workability, and mechanical capabilities. Compressive strength, tensile strength, flexural strength, modules of elasticity, density, toughness, ultrasonic pulse velocity, slump, V funnel, L box, J ring, chloride penetration, air content, and electrical resistance are some of these topics. The results of each property were recorded from the literature and shown in graphs to make a clear comparison for different references which used various mix proportions, mix types, fiber dosages, and types, with aggregate types corresponding to mixture types. The fiber dosages for every literature were recorded in the database and the comparison in the graphs was made according to this fiber dosage. It is important to analysis the behavior of different concretes that contain various fiber types including different aggregates to understand the interaction of all these factors on concrete performance in the form of strength and workability, while looking for long-term behavior and durability. Moreover, understanding the materials behavior is important for leading researchers to further applications in structural concrete. According to the literature, essentially, the best technique to improve compressive strength is to increase the fiber content by up to 1%, and the most common and efficient type of fiber for this purpose is steel fiber. The tensile strength of concrete is greatly enhanced with the addition of fibers, which take the form of a web-like structure resembling a space truss. According to the sources that were examined, concrete’s flexural strength may be increased by up to 1.5% by adding more fiber. Flexural strength has enhanced by 50% to 70% or even more in the majority of investigations. The workability of the concrete has been negatively impacted by the fiber addition. Friction between the aggregates and the fibers provides a good explanation for the great majority of data, which are valid for nearly all types of fibers and concrete. Furthermore, this study investigates how fiber affects concrete durability in the presence of chloride penetration and discovers that adding additional fiber minimizes the amount of tensile and compressive strength loss. Most studies predicted increased concrete density, and the findings showed that high-fiber volume fraction combinations included more air than low-fiber volume fraction mixes. Graphical Abstract